Nepomuceno’s Kyrie: style and intertextuality (Orfeu, 2017)
This article presents an analysis ofthe Kyrie in Alberto Nepomuceno’s Massin D minor (1915), one of the goals beingto identify stylistic features and musicalintertextual relations. In relation to form,texture and timbre, Nepomuceno’s Kyriepresents great similarity to the Kyrie ofLorenzo Perosi, Missa Te Deum Laudamus(1899). As concerns harmony, the piecedenotes a kind of modal character, possibly due to the organ techniques which accompany the gregorian chant. Regardingmelody and prosody, there is a certainproximity to gregorian melodic contours,considered at the time as a paradigm of catholic church music.
Keywords: Musicology; Alberto Nepomuceno; Musical analysis; Mass